CONSUMPTIVE CASH WAQF AS AN INSTRUMENT OF SOCIO-ECONOMIC RESILIENCE: A NORMATIVE ANALYSIS BASED ON THE PRINCIPLE OF MASLAHAH MURSALAH: WAKAF TUNAI KONSUMTIF SEBAGAI INSTRUMEN KETAHANAN SOSIAL-EKONOMI: ANALISIS NORMATIF BERDASARKAN PRINSIP MASLAHAH MURSALAH - Muhammad Alfalah Sebayang; Nispul Khoiri; Dhiauddin Tanjung (SOSIOEDUKASI, 2025)
Consumptive waqf is a type of waqf used to meet the immediate needs of the community, such as the construction of mosques, schools, and temporary social assistance. Although it does not provide sustainable income, consumptive waqf is important for fulfilling basic needs and improving the quality of life. In Indonesia, cash waqf has great potential that can be directed toward urgent needs without violating Islamic principles. This research departs from the urgency of managing consumptive cash waqf in response to economic dynamics, particularly inflation, with a normative juridical approach. This approach emphasizes the analysis of legislation, Islamic legal doctrines, and the principle of maslahah mursalah as a conceptual basis for developing effective and Sharia-compliant waqf management strategies, as well as assessing the impact of inflation on the effects of consumptive cash waqf as a social financing instrument. Based on the results of normative analysis, cash waqf has a clear positive legal basis, among others in Law Number 41 of 2004 concerning Waqf, reinforced by Government Regulation Number 42 of 2006 on the Implementation of the Waqf Law, as well as regulations from the Indonesia Waqf Board (BWI). These regulations recognize the existence of cash waqf and provide a legal framework for its management, including the potential for its consumptive use. However, the consumptive nature of cash waqf is potentially vulnerable to the influence of inflation, which can reduce its utility and effectiveness in meeting social needs. Therefore, the principle of maslahah mursalah becomes important as a balancing instrument between the normative texts of positive law and the practical needs of society in fluctuating economic conditions. The formulation of the management of consumptive cash waqf in accordance with the principles of maslahah mursalah must emphasize the strengthening of nazhir institutions, a transparent oversight mechanism, as well as the integration of community economic empowerment strategies. Based on legislation and a maslahat approach, consumptive cash waqf not only functions as a means of Islamic philanthropy but also as a legal and economic instrument capable of strengthening the socio-economic resilience of communities in facing inflation.